Morphology Evolution of Three-Dimensional Scours Under Submerged Jets - Chen, Ke-ling; Wei, Wang-ru; Deng, Jun (Frontiers in Earth Science, 2022)
Through physical model tests, the three-dimensional morphological features and their scale changes with time were measured and comparatively analyzed during the scouring of a homogeneous granular bed surface using submerged oblique jets. The effects of various flow velocities and water cushion depths on the depth, length, and width of the scour hole were studied. At the early stage of scour formation, the morphological scales changed more dramatically, and the jet impact flow velocity had a more significant effect on the scour hole relative to the depth of the water cushion; for the final scales in all three directions of the scour, the scour depth developed at a more significant rate relative to the length and width of the scour. The correlation between the depth, length, and width of pit formation was achieved based on the time-domain variation pattern of scour hole scales. As the jet velocity increased and the depth of the water cushion decreased, the scour gradually developed from a wide-shallow morphology to a narrow-deep morphology; the impact of three-dimensional morphological features of the scour on hole depth gradually became obvious, appearing to inhibit the development of scour depth. The results of present experimental tests offered an exploratory study of the effect of three-dimensional morphological features on the formation of jet scours, having constituted the basis for more rational analysis and evaluation of energy dissipation for the hydraulic operation in water conservancy projects.